HTERT‐ and hCTLA4Ig‐expressing human bone marrow‐derived mesenchymal stem cells: in vitro and in vivo characterization and osteogenic differentiation. (22nd July 2014) - Dai, Fei; Yang, Sisi; Zhang, Fei; Shi, Dongwen; Zhang, Zehua; Wu, Jun; Xu, Jianzhong
Abstract: Multipotent mesenchymal stem cells (MSCs) are commonly used as seed cells in studies of tissue engineering and regenerative medicine but their clinical application is limited, due to insufficient numbers of autogeneic MSCs, immune rejection of allogeneic MSCs and replicative senescence. We constructed two gene expression vectors for transfection of the human telomerase reverse transcriptase ( hTERT ) and cytotoxic T lymphocyte‐associated antigen 4‐Ig ( CTLA4Ig ) genes into human bone marrow‐derived stem cells (hBMSCs). Successful transfection of both genes generated hTERT–CTLA4Ig hBMSCs that expressed both telomerase (shown by immunohistochemistry and a TRAPeze assay) and CTLA4Ig (demonstrated by immunocytochemistry and western blotting) without apparent mutual interference. Both hTERT BMSCs (92 population doublings) and hTERT–CTLA4Ig hBMSCs (60 population doublings) had an extended lifespan compared with hBMSCs (18 population doublings). Cell cycle analysis revealed that, compared with hBMSCs, a lower proportion of hTERT hBMSCs were in G0 /G1 phase but a higher proportion were in S phase; compared with hTERT hBMSCs, a higher proportion of hTERT–CTLA4Ig hBMSCs were in G0 /G1 phase, while a lower proportion were in S and G2 /M phases. hTERT–CTLA4Ig hBMSCs retained their capacity for osteogenic differentiation in vitro, shown by the detection of hydroxyapatite mineral deposition (labelled tetracycline fluorescence staining), calcareous nodules (alizarin red S staining), alkaline phosphatase (calcium–cobalt method) and osteocalcin (immunocytochemistry). Furthermore, subcutaneous transplantation of hTERT–CTLA4Ig hBMSCs in a rat xenotransplantation model resulted in the successful generation of bone‐like tissue, confirmed using radiography and histological assessment. We propose that allogeneic hTERT–CTLA4Ig hBMSCs may be ideal seed cells for bone tissue engineering. Copyright © 2014 John Wiley & Sons, Ltd.